Обоснование выбора смазочных материалов для буровой технологии - Янгиров Ф. Н. Фарит Наилович; Яхин А. Р. Артур Рамилевич; Мустафин Т. С. Тимур Салаватович; Дихтярь Т. Д. Татьяна Дмитриевна (2018, 2018)
Заглавие с титульного листа